Can Russia compete? - Goldberg, Itzhak Herausgeber; Desai, Raj M., 1966- 1966- Herausgeber (Brookings Institution Press, 2008)
Russia has joined the club of rapidly growing economies, driven by rising prices for oil and gas. Russian authorities are concerned about sustaining this economic performance, however. Thus they have sought to diversify and broaden the basis for growth beyond the profitable natural resource sector and to build an economy that will be able to compete in the twenty-first century. This book presents the case that Russia's neglected manufacturing sector is in need of human capital and policy reforms that will unleash its innovative potential. Can Russia Compete? quantifies and benchmarks the relative strengths and weaknesses of that sector, identifying opportunities to increase Russian productivity and competitiveness.Drawing on original survey data from Russian firms of all sizes, the authors formulate proposals that aim to enhance the innovative potential of russian firms; upgrade the skills of their workforce; and develop a business-friendly climate of lower administrative costs and greater policy certainty.